Astragaloside IV modulates TGF‐β1‐dependent epithelial‐mesenchymal transition in bleomycin‐induced pulmonary fibrosis. Issue 9 (4th July 2018) - Qian, Weibin; Cai, Xinrui; Qian, Qiuhai; Zhang, Wei; Wang, Dongli
Abstract: Epithelial‐mesenchymal transition (EMT) plays an important role in idiopathic pulmonary fibrosis (IPF). Astragaloside IV (ASV), a natural saponin from astragalus membranaceus, has shown anti‐fibrotic property in bleomycin (BLM)‐induced pulmonary fibrosis. The current study was undertaken to determine whether EMT was involved in the beneficial of ASV against BLM‐induced pulmonary fibrosis and to elucidate its potential mechanism. As expected, in BLM‐induced IPF, ASV exerted protective effects on pulmonary fibrosis and ASV significantly reversed BLM‐induced EMT. Intriguing, transforming growth factor‐β1 (TGF‐β1) was found to be up‐regulated, whereas Forkhead box O3a (FOXO3a) was hyperphosphorylated and less expressed. However, ASV treatment inhibited increased TGF‐β1 and activated FOXO3a in lung tissues. TGF‐β1 was administered to alveolar epithelial cells A549 to induce EMT in vitro. Meanwhile, stimulation with TGF‐β1‐activated phosphatidylinositol 3 kinase/protein kinase B (PI3K/Akt) pathway and induced FOXO3a hyperphosphorylated and down‐regulated. It was found that overexpression of FOXO3a leading to the suppression of TGF‐β1‐induced EMT. Moreover, ASV treatment, similar with the TGF‐β1 or PI3K/Akt inhibitor, reverted these cellular changes and inhibited EMT in A549 cells. Collectively, the results suggested that ASV significantly inhibited TGF‐β1/PI3K/Akt‐induced FOXO3a hyperphosphorylation and down‐regulation to reverse EMT during the progression of fibrosis.